Historical paths to shared interest in quality assurance and evaluation - Olli Suominen; Vera Gorodski Centeno; Galina Gurova; Johanna Kallo; Xingguo Zhou (Routledge, 2022)
This chapter explores and outlines the historical background of understanding the development of quality assurance and evaluation (QAE) policies in Brazil, China, and Russia and thus also prepares the ground for the problematics the subsequent chapters analyse. In doing this, we build largely on the previous research literature, albeit occasionally supplementing our analysis with primary documents, such as media reports, policy documents, and parallels found in our interview material. As the following chapters elucidate, although at the level of practical implementation, the countries’ experience differs markedly, at the level of political projects and rhetoric (see Chapter 6), they share a growing interest in QAE. In building the case for future chapters, our foremost task is therefore to ask how these three countries, which until recently developed separately, came to share quite similar domestic expectations and interest in QAE. Drawing on politico-socio-historical approaches, we outline the historical trajectories and antecedents of QAE policies in each national context. Our ambition to trace the socio-historical roots of the phenomenon at hand also resonates with the book’s broader framework, as uncovering the political situation is one of the three analytical dimensions of the CADEP framework the preceding chapter introduced.
Politics of Quality in Education: a Comparative Study of Brazil, China, and Russia